Magnetic tracing of sediment dynamics of mudbanks off southwest coast of India - Badesab, F.; Gaikwad, V.; Gireeshkumar, T.R.; Naikgaonkar, O.; Deenadayalan, K.; Samiksha, S.V.; Kumar, P.K. Dinesh; Loveson, V.J.; Iyer, S.D.; Khan, A.; Udayakrishnan, P.B.; Sardar, A. (My University, 2018)
In this study, we utilized environmental magnetic in combination with sedimentological and hydrodynamic data to investigate the formative processes of mudbanks along southwest coast of India. We document the linkages between enrichment of silt-sized magnetic particles and formation processes of mudbanks along Alappuzha coast. A trend of increasing magnetite concentration and coarsening in magnetic grain size is observed at mudbank stations M2 and M3, while the mud-deficient station (M1) showed an opposite trend. A strong relationship between magnetic and physical grain size for all samples implies that the magnetic particle size and clastic grain size are largely adjunct. Analysis of rock magnetic and grain size data of surficial and suspended sediments from non-mudbank (M1) and two mudbank stations (M2, M3) reflect the differential sediment partitioning and transport regimes which controlled the formation of mudbanks along Alappuzha coast. Two plausible mechanisms responsible for the formation of mudbanks are identified: grain size-selective entrainment is the dominant process during pre-monsoon; weaker hydrodynamics (waves and bottom currents) favors accumulation of silt-sized (fine and coarse) magnetic and non-magnetic fractions resulting in the formation of magnetically low-enriched sediment bed of mixed grain sizes. At the onset of monsoon, wave-induced energetic bottom currents enhance the suspension of entire sediment bedload at stations M2, M3 to form fluid mud. Concurrently, mineral-density-based selective fractionation allows the settling of coarse silt-sized magnetic particles, while the fine magnetic silt-size particles accumulate forming thick fluid mud as a suspension load resulting in the formation of mudbanks. An observed increase in magnetic susceptibility and coarsening in magnetic grain size of surficial sediments at mudbank stations (M2, M3) during monsoon period supports the interpretation. Our findings are summarized in a conceptual model which can be very well applied to investigate sediment dynamics associated with mudbank formation in coastal and shelf sedimentary systems.
Keywords: Environmental magnetism; Mudbanks; Sediment dynamics; Magnetic susceptibility; Grain size